Kepemimpinan Islami Manajer Persada TV Lamongan dalam Kinerja Karyawan - Sutopo, Sutopo; Abdullah, Rizqi; Mubarok, Faizal (Opportunity Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
In a company, a leader is required to be able to develop a company and in developing the company a leader can apply an effective leadership style by applying leadership that emphasizes kinship and togetherness, with such leadership employees will feel comfortable doing their jobs, the company will improve and more developed if employees feel happy in doing the work given by the company. This study contains the following problem formulation: (1). How is the Islamic Leadership Manager of Persada TV Lamongan? (2). What efforts are made by the Manager for employee performance? Thus the problem objectives of this research are (1). To find out how the Islamic leadership of Persada TV managers is applied. (2). To find out what efforts are made by the Manager in the performance of employees who are applied by Persada TV Lamongan. This research is to find out how effective Persada TV Lamongan's leadership is in employee performance, leadership style and performance principles, so that Persada TV Lamongan can develop even more. This study uses qualitative methods, namely the authors analyze data based on information obtained from interviews and documentation studies and the authors use analysis. From the results obtained. Shows that the leadership of the Persada TV Lamongan manager runs quite effectively in the performance of employees which can be seen from the development of Persada TV Lamongan as there are various events or broadcasts that have been scheduled and are still developing at other stages